Advanced Hybrid Closed Loop users' satisfaction of telemedicine and telenursing in pediatric and young adult type 1 diabetes - Marta Bassi; Marta Bassi; Francesca Dufour; Marina Francesca Strati; Daniele Franzone; Marta Scalas; Barbara Lionetti; Giordano Spacco; Francesca Rizza; Prisca Sburlati; Emilio Casalini; Stefano Parodi; et al. (Frontiers Media S.A., 2023)
Background and aimsThe aim of the study was to evaluate the satisfaction of the use of telemedicine and telenursing in children and young adults with Type 1 Diabetes (T1D) using Advanced Hybrid Closed Loop systems (AHCL) with a focus on the role of connectivity, data download and the ease of technical steps in the set and sensor change procedures.MethodsAn online anonymous survey was administered to AHCL users. The questionnaire consisted of five Clusters: Cluster A-B-C included questions related to the general satisfaction in the use of telemedicine, Cluster D was focused on the role of data download and connectivity, Cluster E was related to satisfaction in telenursing and Cluster F to the perception of ease of execution of the technical steps like changing the infusion set and the sensor.ResultsWe collected 136 completed questionnaires. 83.8% of AHCL users were overall satisfied with the quality of the telemedicine service. 88.2% of patients downloaded AHCL data before visits and the overall quality of televisits (data sharing, connectivity, ease of use) was satisfactory for 85.3% of users. Telenursing support during set and sensor change procedures was considered effective by 98% of AHCL users. The sensor and insulin infusion set change procedure is perceived as different for the two systems: set change simpler for Medtronic (p = 0.011) users, while sensor change was simpler for Tandem users (p = 0.009).ConclusionTelemedicine and telenursing have an essential role in diabetology and are highly appreciated in AHCL users. The nurse support in the education of the use of AHCL systems is effective and must be implemented. Unfortunately, not all patients have the technological tools needed for downloading data at home and using telemedicine services; this represents an important challenge for the future of diabetology and for the equity in accessibility to care.